The Legal Framework of the Crime of Cyber Terrorism - Khater, Maya Hassan Mulla (Journal of Economic, Administrative and Legal Sciences, 2018)
Nowadays the terrorist crimes are increasing significantly, while terrorists are using contemporary technology to carry out criminal actions and to achieve their criminal goals, by spreading terror and fear among individuals, institutions and even governments of the countries. Therefore this research is showing up the tools and ways in which terrorist organizations are using in their electronic crimes. And also the importance of the international cooperation to prevent the current terrorist crimes, which has become very dangerous for the whole world, according to how easy it is to commit, and because it can reach quickly to all segments of the society, and it has low cost, and it is very difficult to discover its offenders, especially if we take into account the easily of creating websites and the spreading of spyware and the destruction of sites, systems and information, and the ability to broadcast statements ,declarations ,movies ,and dissemination through it.